Project-Based Learning and Writing Skills: A Relationship in Junior High School Students - Fatimah, Siti (English Language and Literature in Education Journal, 2024)
Project-Based Learning (PjBL) effectively integrates students’ knowledge, attitudes, and skills, creating a productive and engaging learning environment. This study investigates the influence of PjBL on the writing skills of 9th-grade students at SMP Negeri 44 Surabaya, employing a pre-experimental design with a sample of 40 Grade IX-A students. Statistical analysis revealed a significant enhancement in students’ writing skills, with the post-test mean score rising to 85.5 from a pre-test mean score of 72.6, and a Sig. (2-tailed) value of .001. The acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho) confirms that PjBL significantly boosts writing proficiency. These findings highlight the potential of PjBL to improve academic performance by fostering active learning and critical thinking. It is recommended that educators integrate PjBL into the curriculum to enhance not only writing skills but also broader academic competencies. Future research should investigate PjBL’s effectiveness on other English language skills and its potential to cultivate critical thinking and problem-solving abilities. Furthermore, exploring its application across different educational contexts and age groups could provide a more comprehensive understanding of its benefits and limitations. Adopting PjBL can transform traditional teaching methods, making learning more dynamic and student-centered, ultimately leading to better educational outcomes.